2022
DOI: 10.1021/acs.orglett.1c04321
|View full text |Cite
|
Sign up to set email alerts
|

Ir-Catalyzed Remote Functionalization by the Combination of Deconjugative Chain-Walking and C–H Activation Using a Transient Directing Group

Abstract: An Ir-catalyzed reaction of N-benzylideneanilines with functionalized alkenes such as α,β-unsaturated esters gave ortho-substituted benzaldehyde derivatives with a functional group at the remote position after acidic treatment. The present transformation involves deconjugative long-range isomerization (chain-walking) up to 11 times and C−H activation using an imino group as a transient directing group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…8 Very recently, Shibata and co-workers have extended the aromatic substrate to N -benzylideneanilines for the formation of linear alkyl-substituted benzaldehyde (Scheme 1c). 9 In contrast to the well-developed single hydroarylation of α-alkenes, the tandem transformation with internal alkenes can generate a new C sp 2 –C sp 3 bond at an initially inert C sp 3 −H bond, thus providing an attractive means of remote C sp 3 −H bond functionalization. 10 Despite these remarkable contributions, transition metal-catalyzed tandem isomerization/ anti -Markovnikov hydroarylation of unactivated internal alkenes with heteroarenes for the preparation of linear alkylheteroarenes has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…8 Very recently, Shibata and co-workers have extended the aromatic substrate to N -benzylideneanilines for the formation of linear alkyl-substituted benzaldehyde (Scheme 1c). 9 In contrast to the well-developed single hydroarylation of α-alkenes, the tandem transformation with internal alkenes can generate a new C sp 2 –C sp 3 bond at an initially inert C sp 3 −H bond, thus providing an attractive means of remote C sp 3 −H bond functionalization. 10 Despite these remarkable contributions, transition metal-catalyzed tandem isomerization/ anti -Markovnikov hydroarylation of unactivated internal alkenes with heteroarenes for the preparation of linear alkylheteroarenes has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…When DMF-d 7 was used as the reaction solvent, amidation (3) took place without deuteration (Scheme 4B), indicating that DMF did not serve as the hydride source. However, when D 2 O was employed as an additive in lieu of H 2 O, deuterium incorporation was also observed mainly at the α-carbon to the OTIPS group (Scheme 4C), suggesting that water may undergo a hydride exchange with the Ir−H species, 42,47,91 which is in situ generated from a reaction of [Cp*IrCl 2 ] 2 with HBpin. 92 In addition, when deuterated substrates 65 and O-silyl enol 1 were used together in a crossover reaction, no deuterium was incorporated in the amidated product 3 (Scheme 4D).…”
Section: ■ Introductionmentioning
confidence: 99%
“…38 Computational Studies on Terminal-Selective Amidation. With the above experimental mechanistic studies and literature precedents, 47,54,91 we additionally explored the plausible mechanism of the current terminal-selective amidation using density functional theory (DFT) calculations (Figure 1). Given that a hydride species A [Cp*Ir(Cl)(H)] is postulated to be generated at the beginning from the iridium precursor and hydride sources, 92,95,96 Gibbs energies in the chain walking process are summarized in Figure 1A.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The hydridoiridium intermediate triggered deconjugative isomerization of the double bond, giving the terminal alkene. Next, anti-Markovnikov addition forged linear addition products selectively . To the best of our knowledge, the synergistic strategy of C–H activation and consecutive isomerization to give a Markovnikov product has not yet been reported (Scheme C). , As an extension of this study, and due to our continued interest in cationic iridium-catalyzed C–H activation reactions, ,, we further elaborated this synergistic strategy of C–H activation and consecutive isomerization.…”
mentioning
confidence: 99%
“…We re-evaluated different directing groups and found that a carbamoyl directing group can also trigger consecutive isomerization. The reaction conditions were the same as those in the previous study, and the starting material was replaced by benzanilide ( 1a ). A mixture of isomers can be generated, including the isomerized product with a branched isomer 3 and a linear isomer 3′ and the nonisomerized product 3′′ .…”
mentioning
confidence: 99%